Direct one-step synthesis of a formally fully bio-based polymer from cellulose and cinnamon flavor. Issue 18 (7th August 2019) - Hirose, Daisuke; Kusuma, Samuel Budi Wardhana; Ina, Daiki; Wada, Naoki; Takahashi, Kenji
Abstract : Direct fully bio-based polymer synthesis by cellulose modification involving simply mixing cellulose and cinnamaldehyde "cinnamon flavor" in an ionic liquid. Abstract : A method of cellulose modification involving simply mixing cellulose with cinnamaldehyde, i.e., "cinnamon flavor", in an ionic liquid has been developed. An oxidative esterification reaction proceeds between cellulose and cinnamaldehyde to directly provide the highly substituted and formally fully bio-based cellulose ester with perfect atom economy.